Temperature-Driven Hydrocarbon Generation-Expulsion and Structural Transformation of Organic-Rich Shale Assessed by in situ Heating SEM - Yuan, Yuan; Yang, Jijin (Frontiers in Earth Science, 2021)
Mud shale can serve as source or cap rock but also as a reservoir rock, and so the development of pores or cracks in shale has become of great interest in recent years. However, prior work using non-identical samples, varying fields of view and non-continuous heating processes has produced varying data. The unique hydrocarbon generation and expulsion characteristics of shale as a source rock and the relationship with the evolution of pores or cracks in the reservoir are thus not well understood. The present work attempted to monitor detailed structural changes during the continuous heating of shale and to establish possible relationships with hydrocarbon generation and expulsion by heating immature shale samples while performing in situ scanning electron microscopy (SEM) imaging and monitoring the chamber vacuum. Samples were heated at 20 °C/min from ambient to 700 °C with 30 min holds at 100 °C intervals during which SEM images were acquired. The SEM chamber vacuum was found to change during sample heating as a consequence of hydrocarbon generation and expulsion. Two episodic hydrocarbon expulsion stages were observed, at 300 and 500 °C. As the temperature was increased from ambient to 700 °C, samples exhibited consecutive shrinkage, expansion and shrinkage, and the amount of structural change in the vertical bedding direction was greater than that in the bedding direction. At the same time, the opening, closing and subsequent reopening of microcracks was observed. Hydrocarbon generation and expulsion led to the expansion of existing fractures and the opening of new cracks to produce an effective fracture network allowing fluid migration. The combination of high-resolution SEM and a high-temperature heating stage allowed correlation between the evolution of pores or cracks and hydrocarbon generation and expulsion to be examined.